KARAKTERISTIK RESPONDEN DENGAN KEJADIAN HIPERTENSI DI DESA PATOKAN, PROBOLINGGO TAHUN 2015 - Kuuni Ulfah Naila Elmuna (Universitas STRADA Indonesia, 2016)
Hypertension is main risk factor cause mortality in the world. One of the consequence of hypertension are stroke and coronary heart attack. Hypertensions prevalence rate 2013 in Indonesia decreased 5,9% from 2007. Probolinggo became top ten rank with the most stroke prevalence from 38 district in East Java. This research goal was to identify respondent characteristic and hypertension in Patokan village, Bantaran subdistrict, Probolinggo district. Used observasional-descriptive method with utilized questionare and blood pressure measurement. Independent variable : sex, age, job ownership, type of job and salary every month and also hypertension status as dependent variable. The respondent were 20 people. The result show that most of respondent have characteristic as women, more than 40 years old, physically work type and monthly salary lower than regional minimum salary. Necessary to control the sum of hypertension sufferer with routine blood pressure check, organize eating behaviour and give education about hypertension since early